The European Union Innovation Performance in View of the Lisbon Strategy; Innowacyjnosćǵospodarek Unii Europejskiej w sẃietle Strategii Lizbonśkiej - Witold Kasperkiewicz; Andrzej Kacprzyk (Comparative Economic Research. Central and Eastern Europe, 2010)
The Lisbon Strategy was accepted by the European Council in March 2000 during the Lisbon summit. The Strategy is European Union's answer to many challenges resulting from the economic globalization and the dynamic development of information technologies. The importance of these challenges is paramount. Hence, it has turned out that new strategies based on the principle of balanced development which would modernize the European economy are indispensable. Even though in the last decade of the 20th century integration process of Union's economies underwent considerable intensification, they still could not outweigh the American economy in the technological race. As a result European economies became less competitive in comparison with the American counterpart. The rise in innovativeness of the EU economies plays a key role in the implementation of the major aims of the Lisbon Strategy. The ability to facilitate those innovations and to put them into practice have crucial importance for minimizing the economic distance between EU and US. The main aim of the paper is to present the innovativeness of European economies and Japan. The paper also evaluates the conditions and effects of the implementation of the strategic objectives of Lisbon Strategy. The paper is divided into four parts. First deals with the characteristics of the role of knowledge-based economy and innovativeness of the economic system in Lisbon Strategy. Second is devoted to the issue of innovativeness of the EU economies as compared to the US and Japan. Third presents evaluation of the Lisbon Strategy implementation. Fourth analyses the renewed Lisbon Strategy – – Strategia Lizbonśka, przyjeta przez Rade Europejska w marcu 2000 roku podczas szczytu w Lizbonie, stanowi odpowiedzÚnii Europejskiej na liczne wyzwania wynikajace z globalizacji procesoẃ gospodarczych i dynamicznego rozwoju technologii informacyjnych. Znaczenie owych wyzwanj́est tak duzė, zė niezbedne okazało sie przygotowanie strategii modernizacji europejskiej gospodarki, opartej na zasadzie zroẃnowazȯnego rozwoju. Wprawdzie w dekadzie lat 90. ubiegłego stulecia pogłebieniu uległy procesy integracyjne gospodarek Wspoĺnoty, to jednak nie potrafiły one doroẃnacǵospodarce amerykanśkiej w wysćigu technologicznym. Wskutek tego gospodarki zachodnioeuropejskie stały sie mniej konkurencyjne w poroẃnaniu z amerykanśka. Strategia Lizbonśka jest najbardziej rozwinietym w historii Unii Europejskiej programem zwiekszenia konkurencyjnosći gospodarek europejskich. Istotna role w realizacji celoẃ Strategii Lizbonśkiej odgrywa poprawa innowacyjnosći gospodarek Zdolnosćt́worzenia i praktycznego wykorzystania innowacji ma kapitalne znaczenie dla zmniejszenia dystansu ekonomicznego i technologicznego miedzy Unia Europejska a USA. Celem artykułu jest przedstawienie istoty Strategii Lizbonśkiej (wersji pierwotnej i zmodyfikowanej), ukazanie poziomu innowacyjnosći gospodarek Unii Europejskiej na tle USA i Japonii, a takzė dokonanie oceny dotychczasowych rezultatoẃ w zakresie realizacji postanowienówej Strategii. Artykuł składa sie z wprowadzenia, czterech czesći i zakonćzenia. Czesćṕierwsza posẃiecona jest prezentacji roli gospodarki opartej na wiedzy i innowacyjnosći w Strategii Lizbonśkiej. Czesćd́ruga zawiera analize poziomu innowacyjnosći gospodarek UE na tle USA i Japonii. W czesći trzeciej przedstawiono ocene realizacji głoẃnych celoẃ Strategii Lizbonśkiej, a w czwartej załozėnia nowej wersji owej Strategii.
Keywords: 330